1990
DOI: 10.1002/1097-0142(19900201)65:3<492::aid-cncr2820650320>3.0.co;2-c
|View full text |Cite
|
Sign up to set email alerts
|

Kaposi's sarcoma in immunosuppression possibly the result of a dual viral infection

Abstract: Kaposi's sarcoma of the gingiva and skin developed in an HIV-negative renal transplant patient while he was receiving cyclosporine therapy. The Kaposi's sarcoma developed shortly after the patient had an acute infection with cytomegalovirus (CMV). Electron microscopy of the tumor's established cell line showed two types of virus-like particles. CMV DNA was identifiable in the cell line whereas infectious CMV could be isolated only after repeated passages (only after 3 months of culture). The other virus could … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

1991
1991
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(39 citation statements)
references
References 14 publications
0
39
0
Order By: Relevance
“…KS-SLK was obtained from Dr. Rubinstein. 29 MCF7, HT29, and SCC-15 were from American Type Culture Collection (Manassas, VA). All cells were propagated in RPMI-1640, supplemented with 10% Fetal Bovine Serum, 100 units/ml of penicillin and 100 g/ml streptomycin from Cellgro (Manassas, VA).…”
Section: Cell Culturementioning
confidence: 99%
“…KS-SLK was obtained from Dr. Rubinstein. 29 MCF7, HT29, and SCC-15 were from American Type Culture Collection (Manassas, VA). All cells were propagated in RPMI-1640, supplemented with 10% Fetal Bovine Serum, 100 units/ml of penicillin and 100 g/ml streptomycin from Cellgro (Manassas, VA).…”
Section: Cell Culturementioning
confidence: 99%
“…The human KS-derived SLK cell line [11,12] was obtained from Donald Ganem's laboratory (UCSF) and cultured in DMEM-High Glucose supplemented with 10% fetal bovine serum, penicillin G (100 units/ml), and streptomycin (100 μg/ml). Human umbilical vein endothelial cells (HUVEC) were obtained from Cambrex (Walkersville, MD) and cultured in EGM media (Cambrex).…”
Section: Cells and Reagentsmentioning
confidence: 99%
“…These studies were conducted in the human KS biopsy-derived SLK cell line. SLK cells are KSHV negative, diploid, of endothelial origin, and form KS-like tumors in nude mice [11,12]. Since KS is a virus-associated disease, we were particularly interested in analyzing any functional viral pattern recognition receptors.…”
Section: Introductionmentioning
confidence: 99%
“…A number of Iaboratories have cultured cells from Kaposi' s sarcoma that express markers characteristic for vascular or lymphatic endothelium (Delli-Bovi et al, 1986;Nakamura et al, 1988;Roth et al, 1988;Siegal et al, 1990;Corbeil et al, 1991;Herndier et aL., 1994a), but cultures expressing smooth muscle (X-actin (Albini et al, 1988;Wittek et aL., 1991) as weIl as mixed populations (Siegal et al, 1990; further references in Roth et al, 1992) have also been reported. The 1ineage identity of cuItured cells has been defined by staining for the same markers as in the in-situ studies, notably vimentin and cytokeratin (for discrimination of mesenchymal and epithelial cells respectively), the endotheIiaI markers vWF, PaI-E, OKM-5, BMA 120 (specific for bIoodvessel endotheIium), and ENA and UEA-I Iectin (reactive with bIood-vesseI and Iymphatic endotheIium), CD14, CD68 and factor XIIla (for the monocyte/macrophage lineage), SMC (X-actin (smooth muscle and myofibroblast) and others (reviewed by Roth et al, 1992;StürzI et al, 1992a;Kaaya et aL., 1995).…”
Section: Time Of Onset Of Cancers In Non-hiv-associated Immunodeficiencymentioning
confidence: 99%
“…SpindIe-shaped cells showing a moderate expression of endotheIiaI antigens have been cultured from peripheral blood of Kaposi's sarcoma patients (Browning et al, 1994). (Siegal et al, 1990;Herndier et aL., 1994a). This cell line had a normal diploid karyotype and expressed the endotheIiaI markers factor VIII, EN-4 and UEA-I Iectin.…”
Section: Time Of Onset Of Cancers In Non-hiv-associated Immunodeficiencymentioning
confidence: 99%